Incidence and sociodemographic factors of mechanical restraints in the emergency department: a retrospective single-centre Swiss cohort (Swiss Medical Weekly, 2026)
STUDY AIMS: To determine the incidence of mechanical restraint in the emergency department (ED) of the University Hospital of Bern, Switzerland; To assess differences in restraint frequency and practice across patient groups (sex, age, alcohol involvement); To characterise triggers of aggression or agitation and restraint-related interventions including medication use; To examine temporal patterns, particularly the impact of the COVID-19 lockdown and pandemic.METHODS: We included patients presenting at our institution between 1 January 2018 and 30 September 2022 who were subjected to mechanical restraint. Patients were identified through a keyword search followed by a comprehensive full-text review of the hospital database. Demographic and consultation characteristics, data about restraining circumstances and characteristics, as well as referral or discharge procedure were collected. Group comparisons were performed using the Wilcoxon rank-sum test or Kruskal–Wallis test, as appropriate. Categorical variables were compared using the chi-squared test. Incidence rate ratios across the three COVID-19 mitigation phases (pre, during, post) were estimated using Poisson regression.RESULTS: We identified 285 patients who were subjected to mechanical restraint, corresponding to an incidence of 1.22 (95% CI: 1.08–1.37) per 1000 ED consultations during the study period. Men were overrepresented with 67.4% and the median age was 30 years (IQR: 23–41). Alcohol intoxication was the primary trigger of aggression in 35.4% of cases, with mixed intoxication present in 24.2%. The largest subgroup consisted of young men (≤40 years) under the influence of alcohol (31.6%). Compared to men, women were generally younger (28 vs 32 years, p